2013
DOI: 10.1093/scan/nst133
|View full text |Cite
|
Sign up to set email alerts
|

‘If you are good, I get better’: the role of social hierarchy in perceptual decision-making

Abstract: So far, it was unclear if social hierarchy could influence sensory or perceptual cognitive processes. We evaluated the effects of social hierarchy on these processes using a basic visual perceptual decision task. We constructed a social hierarchy where participants performed the perceptual task separately with two covertly simulated players (superior, inferior). Participants were faster (better) when performing the discrimination task with the superior player. We studied the time course when social hierarchy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
3
24
0
2
Order By: Relevance
“…Both effects may be due to the fact that participants in the experimental condition increased their task effort compared to those in the control condition because majority members were able to track participants' performance in the former but not in the latter condition. This interpretation is supported by two recent studies showing that the presence of peers during a task leads to increased effort (Gilman et al, 2015) and increased early attentional resources (Santamaria-Garcia et al, 2013).…”
Section: Social Influence Increases Intensity Of Stimulus Processingsupporting
confidence: 55%
See 2 more Smart Citations
“…Both effects may be due to the fact that participants in the experimental condition increased their task effort compared to those in the control condition because majority members were able to track participants' performance in the former but not in the latter condition. This interpretation is supported by two recent studies showing that the presence of peers during a task leads to increased effort (Gilman et al, 2015) and increased early attentional resources (Santamaria-Garcia et al, 2013).…”
Section: Social Influence Increases Intensity Of Stimulus Processingsupporting
confidence: 55%
“…Additionally, to the best of our knowledge, previous studies or reviews neither reported nor discussed gender differences in the neurocognitive mechanism of social influence (e.g. Schnuerch and Gibbons, 2014;Trautmann-Lengsfeld and Herrmann, 2014). Thus, although research using the Asch paradigm consistently revealed higher levels of conformity for female than for male participants (Bond and Smith, 1996), there is insufficient evidence to suggest that this difference is due to qualitative gender differences in the mediating neurocognitive mechanisms.…”
Section: Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Unknown to the participants, the outcome of the task was manipulated such that all participants were ranked as a medium. A similar procedure has been employed in previous studies, and participants have been demonstrated to be strongly engaged in this social hierarchical context (Zink et al, 2008;Breton et al, 2014;Santamaria-Garcia et al, 2014;Feng et al, 2016).…”
Section: Establishing Social Statusmentioning
confidence: 99%
“…Social status is the relative rank of an individual along one or more dimensions within a given social hierarchy, which can strongly modulate human socio-emotional functioning and attention/cognitive processes (Zink et al, 2008;Boksem et al, 2012;Santamaria-Garcia et al, 2014;Feng et al, 2015Feng et al, , 2016. More importantly, social status is a factor that influences how we evaluate the behavior of others (Mattan et al, 2017;Ren et al, 2018;Rizzo and Killen, 2018).…”
Section: Introductionmentioning
confidence: 99%